2016
DOI: 10.1504/ijlsm.2016.075660
|View full text |Cite
|
Sign up to set email alerts
|

Optimistic and pessimistic performance and congestion analysis in fuzzy data envelopment analysis

Abstract: The notion of input congestion in data envelopment analysis (DEA) is analogous to the 'law of diminishing returns' in the classical economic theory of production which states that if a single input is increased while other inputs are held constant, the marginal product of the variable input diminishes. Congestion has been an under-researched topic in economic theory especially when there is a need for augmenting inputs to serve important objectives besides output maximisation. We propose a fuzzy DEA model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Kao and Liu (, ), Smirlis et al (), and Khodabakhshi, Tavana, and Abootaleb () suggested that, when the inputs and outputs vary in an interval, the minimum efficiency of a DMU k occurs when the outputs of this DMU and the inputs of other DMUs are set to their lower bounds, whereas the inputs of the DMU k and the outputs of other DMUs are set to their upper bounds. On the contrary, the maximum efficiency of a DMU k occurs when the outputs of this DMU and the inputs of other DMUs are set to their upper bounds, whereas the inputs of this DMU and the outputs of other DMUs are set to their lower bounds.…”
Section: Solution and Ranking Proceduresmentioning
confidence: 99%
“…Kao and Liu (, ), Smirlis et al (), and Khodabakhshi, Tavana, and Abootaleb () suggested that, when the inputs and outputs vary in an interval, the minimum efficiency of a DMU k occurs when the outputs of this DMU and the inputs of other DMUs are set to their lower bounds, whereas the inputs of the DMU k and the outputs of other DMUs are set to their upper bounds. On the contrary, the maximum efficiency of a DMU k occurs when the outputs of this DMU and the inputs of other DMUs are set to their upper bounds, whereas the inputs of this DMU and the outputs of other DMUs are set to their lower bounds.…”
Section: Solution and Ranking Proceduresmentioning
confidence: 99%